Palaeobiogeography of Ordovician echinoderms - Lefebvre, B. (2013)
The palaeobiogeographical distribution of the six major clades of Ordovician echinoderms (asterozoans, blastozoans, crinoids, echinozoans, edrioasteroids and stylophorans) is analysed based on a comprehensive and up-to-date database compiling 3701 occurrences (1938 species recorded from 331 localities) of both complete specimens and isolated ossicles. Although historically biased towards a limited number of regions (Europe, North America, Russia), the resulting dataset makes it possible to identify six main palaeobiogeographical provinces for Ordovician echinoderms: Laurentia, Baltica, West Gondwana, East Gondwana, Avalonia and Siberia. At a global scale, the high endemicity of echinoderms during the Early to Middle Ordovician coincides with the time of maximum dispersal of continental masses. Late Ordovician faunas tend to become more cosmopolitan, possibly as a consequence of changing palaeogeography and/or relatively higher sea-levels in the Sandbian-Katian interval. Regional biodiversity patterns of Ordovician echinoderms confirm that their major diversification during the Ordovician is not a single, universal evolutionary event, but rather results from the complex addition of contrasted local evolutionary trends Â©The Geological Society of London 2013.